Advanced Techniques in Biophysics - Arrondo, José Luis R.; Alonso, Alicia (Springer Series in Biophysics, 2006)
Technical advancements are basic elements in our life. In biophysical studies, new applications and improvements in well-established techniques are being implemented every day. This book deals with advancements produced not only from a technical point of view, but also from new approaches that are being taken in the study of biophysical samples, such as nanotechniques or single-cell measurements. This book constitutes a privileged observatory for reviewing novel applications of biophysical techniques that can help the reader enter an area where the technology is progressing quickly and where a comprehensive explanation is not always to be found.